Teaching strategies and mathematics achievement of junior high school students in the regular class program - Barroga, Eden Labiano Romarate (Urdaneta City : [s.n.], 2017)
This study aimed to determine the teaching strategies and mathematics achievement of Junior High School students in the regular class program. It specifically ascertained the teaching strategies of Mathematics teachers and mathematics achievement of the JHS students during the first quarter grades of the School Year 2016-2017; the relationship between the teaching strategies and mathematics achievement of JHS students and the problems encountered by the teachers and students in teaching and learning Mathematics. The researcher made used of descriptive survey, documentary analysis and appropriate statistical instruments in determining and processing the data. Generally, teachers oftentimes used Mathematics teaching strategies such as classroom-based learning, interest learning centers techniques and field study, cooperative learning and interactive and innovative learnings which were considered comparatively effective. These were oftentimes perceived by the students as instructional approaches by the Mathematics teachers. Additionally, appropriate teaching strategies adopted by Mathematics teachers play important role in influencing students academic achievement particularly to JHS students with conditional grades; there was a significant relationship between teaching strategies and academic achievement of the students in Mathematics wherein teaching strategies affect the Mathematics achievement of the JHS students; and Mathematics students become overly dependent and slightly boring on the teachers teaching practices and presentation and discussion on the subject matter. Because of this, constant capacity building focusing on the Enhancement and Development of Effective and Necessary (EDEN) Mathematics teaching strategies was proposed to help Mathematics teachers enhance their competences in teaching the subject.
Bibliography: pages 60-62.
CHED-La Union
Keywords: Teaching strategies